2015
DOI: 10.1002/app5.101
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Links between Bilateral and Regional Trade Agreements and Merchandise Trade

Abstract: Over 200 bilateral and regional trade agreements are currently in force, yet their impact remains a topic of debate. We analyse effects of 27 agreements that are of particular importance for Australia on the value of merchandise trade flows using data from 1970 up to the global financial crisis in 2008. We show that preferential trade agreements generally increase trade between members but that there are often offsetting negative effects on trade with non-signatories. In contrast to regional trading blocs and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 28 publications
(42 reference statements)
1
9
0
1
Order By: Relevance
“…As expected, distance exerted a substantial negative impact on agricultural export. This result supported the views of Barbalet et al (2015) and Natos et al (2014), who pointed out that the higher the distance, the higher the transaction costs and the less trade. According to the authors’ estimates, a 1% increase in the distance has the effect of a 0.844% decrease in agriculture exports.…”
Section: Resultssupporting
confidence: 89%
“…As expected, distance exerted a substantial negative impact on agricultural export. This result supported the views of Barbalet et al (2015) and Natos et al (2014), who pointed out that the higher the distance, the higher the transaction costs and the less trade. According to the authors’ estimates, a 1% increase in the distance has the effect of a 0.844% decrease in agriculture exports.…”
Section: Resultssupporting
confidence: 89%
“…Entry by a USMCA member into a free trade agreement with a non-market country will allow the other members to terminate USMCA agreement and replace it with a bilateral agreement as between them. Kahouli & Maktouf, 2014a;Barbalet, Greenville, Crook, Gretton, & Breunig, 2015). Within this approach, various models and specifications have been proposed.…”
Section: The Gravity Modelmentioning
confidence: 99%
“…Similarly, bilateral trade volumes and the landscape of GVCs will be influenced by the relative size of markets and the economic distance between them, along with cultural factors, such as shared history, a shared language and shared borders (Anderson, 1979). Empirical studies have shown that these structural factors are strong determinants of trade, including for agro-food trade (Barbalet et al, 2015;Carrere, 2006;Cheng and Wall;, Anderson, 1979. However, backward and forward participation indexes pick up different effects.…”
Section: Structural Factorsmentioning
confidence: 99%